2012
DOI: 10.1142/s0219519411004563
|View full text |Cite
|
Sign up to set email alerts
|

Effect on Plantar Pressure Distribution With Wearing Different Base Size of High-Heel Shoes During Walking and Slow Running

Abstract: High heeled shoes may alter the regular loading pattern of the plantar pressure, especially increased in the forefoot area. Walking with narrow base of high heeled shoes may induce the brisk acceleration of the supported leg due to instability that increases the force on the plantar area. Particularly, this phenomenon may be amplified while slow running, but never been investigated. Materials and Methods: Plantar pressures were measured for different specific area of foot using the Pedar-X system. The effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Luximon et al noted that the maximal peak pressure uniformly increased over the whole plantar in large HBS, whereas a narrowed HBS presented higher maximal peak pressure in the toe region [ 30 ]. This result is partially similar to Guo et al whose research showed that the plantar pressure of hallux was significantly increased in small HBS compared to large HBS [ 29 ]. Except for the impact of heel height, the narrow HBS may be a direct reason contributing to hammer toe which is caused by excessive pressure on the metatarsal-phalangeal region during walking with HH.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Luximon et al noted that the maximal peak pressure uniformly increased over the whole plantar in large HBS, whereas a narrowed HBS presented higher maximal peak pressure in the toe region [ 30 ]. This result is partially similar to Guo et al whose research showed that the plantar pressure of hallux was significantly increased in small HBS compared to large HBS [ 29 ]. Except for the impact of heel height, the narrow HBS may be a direct reason contributing to hammer toe which is caused by excessive pressure on the metatarsal-phalangeal region during walking with HH.…”
Section: Discussionsupporting
confidence: 89%
“…Two studies were associated with the effect of HBS on distribution of plantar pressure patterns, COP trajectory, and perceived comfort. A large HBS demonstrated smaller maximal peak pear pressure in the rearfoot, midfoot, and forefoot compared to small HBS [ 29 , 30 ]. It must be noted that the scale of HBS affects the COP location in the anterior-posterior direction at the end of the stance phase.…”
Section: Resultsmentioning
confidence: 99%
“…Despite of wearing experience, however, running on moderate high heels definitely increases risks of knee osteoarthritis and ankle sprain. The heel geometry including height (Gu, Zhang & Shen, 2013;Stefanyshyn et al, 2000), base size (Guo et al, 2012;Luximon et al, 2015) and even angle between the sole and heel etc. should be integrated in high-heel shoes design for individuals with different wearing experience.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, there was a distinctive difference between the data for the M2-3 regions of this work and previous researches on high heeled walking, in which no significant difference was observed in the M2-3 regions. This difference could be due to the fact that the plantar pressure focused on the medial forefoot much more during jogging with higher values than walking [23]. The alterations of the pressure distibution might lead to the discomfort of the foot and may cause some foot injuries such as plantar fasciitis [24].…”
Section: Discussionmentioning
confidence: 99%